Azerbaijan: Recent economic developments and policy issues in sustainability of growth - Rupinder Singh; Juhani Laurila (Bank of Finland, Institute for Economies in Transition (BOFIT), 1999)
The macro economic stabilisation in Azerbaijan has been successful. Following cessation of conflict with Armenia, and decline of GDP by 60 per cent from 1990 to 1995, the government in effect implemented a big-bang reform process in 1995.The inflation rate has now declined to the lowest rate of any transition country and important reforms in the monetary-fiscal mix have been undertaken.The second plank of first generation reforms, liberalisation, has also been successfully implemented with liberalisation of prices, the trade and foreign exchange regimes and virtual completion of small-scale privatisation, although the onset of the Russian crisis in 1998 has impacted negatively both internal and external balances.The paper presents the current economic picture for Azerbaijan and then assesses economic policy issues facing the country. Azerbaijan is well endowed with natural resources, particularly oil but also gas.The second part of the paper considers the question by focussing on policy issues related to the potential flow of oil-based monies into Azerbaijan.The possibility of the "Dutch Disease" syndrome impacting Azerbaijan through a rising real exchange rate on the non-oil sector is not considered to be a problem at present but is expected to become a policy concern in the medium- to long term.Structural reforms in public finance to deal with expected surpluses are lagging and are necessary in the next phase of the transition of Azerbaijan.Moreover, significant reforms are required in banking - privatisation, improvement in regulation and supervision and in the implementation of supporting legal rights, given the current lack of financial intermediation.
URN:NBN:fi:bof-201408071905
Keywords: 330; Azerbaijan; economic development; oil; Dutch Disease; transition economies